On Alasdair Maclntyre’s "After virtue" - Machura, Piotr (Folia Philosophica, 2002)
The author presents here MacIntyre’s views expressed in his most extensively discussed work "After Virtue". The author of the present article concentrates on the British philosopher’s views concerning the modern condition of the moral discourse, the origin of which MacIntyre identifies in the rejection of the pre-modem moral system derived from Aristotle. The philosopher, indicating those elements of the history of culture which led to the rejection of that scheme, attempts, being convinced of the social origin of ethics, to reconstruct the way of thinking that would conform with the Aristotelian categories, and to restore the notion of practice on which has founded his concept of virtues and of the narrative unity of human life. In its last part, the author points to the most controversial elements of the presented conception and expresses his criticism of some of MacIntyre’s statements.